Examining New Public Diplomacy and Interfaith Dialogue in Indonesia: Cases of World Peace Forum (WPF) and Religion Twenty (R20) - Ridwan, Ridwan; Hanan, Djayadi; Astuti, Tri Sulistianing (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2024)
This paper delves into the relationship between new public diplomacy and interfaith dialogue in Indonesia by explicating the cases of the World Peace Forum and Religion Twenty. Using qualitative methods, the article holistically explores the emergence, goals, actors, and dynamics of both religious organizations’ diplomacy. This study demonstrates that both forums aim to promote world peace by introducing “Moderate Islam” as the face of Indonesian diplomacy. The findings in this paper also show several strengths and weaknesses of the two forums. This paper analyses the topic from a broader perspective by using the new public diplomacy theory and theory of change from the perspective of interfaith dialogue. Hence, this paper concentrates on enriching the academic understanding of interfaith diplomacy as a reference in the development of interfaith diplomacy in other countries.